Pemetaan Minat Belajar Ekonomi pada Mahasiswa Universitas Swasta di Kota Medan Berdasarkan Karakteristik Individu: Suatu Studi Deskriptif - Muhammad Fitri Rahmadana (Outline Journal of Management and Accounting, 2022)
The aim of this study is to explore the learning interests of accounting students based on individual characteristics. The population of this study is comprised of lecturers and students from the accounting program within the faculty of economics at private universities in Medan. Random sampling was used to select the participants. Data collection techniques included observation, documentary study, interviews, and questionnaires. Qualitative descriptive analysis was used to analyze the data. The results of the study showed that students are interested in learning accounting, although there are still some topics that they find difficult to understand. This is due to the fact that students come from different educational backgrounds and have different genders, and that their learning activities tend to only involve listening to lectures, taking notes, and doing assignments. Therefore, it is necessary to implement varied and innovative learning activities. A learning design using a learning model is needed to help lecturers create an effective, efficient, and engaging learning program, so that the learning outcomes for the introductory accounting course can be achieved.